Workbook Fisika Menggunakan Representasi Multimodus pada Topik Gerak Harmonik Sederhana - Metta Liana; Parlindungan Sinaga; Emiliannur Emiliannur (Postgraduate, University of Mataram, 2023)
This study aimed to produce teaching materials in workbooks using multimodal representations, which can effectively improve problem-solving and critical-thinking skills. The research method used is the research and development (R&D) method. Test the quality of the workbook developed through validation by three expert lecturers and ten teachers and test the legibility of the main ideas of the discourse by ten high school students. Meanwhile, to test the effectiveness of this research workbook using design randomized control group pretest-posttest design to 70 high school students, 35 each in the control class and 35 in the experimental class. The test results of students' problem-solving and critical-thinking skills were analyzed quantitatively using the N-gain and t-test with the help of SPSS. Based on the main idea's quality and understanding tests, the feasibility percentage of the workbook was 76.35% in the feasible category. Moreover, the effectiveness test results show that workbooks using multimodal representations significantly improve students' problem-solving skills and critical-thinking skills compared to worksheets that can be used in schools.